Influence of Nigerian Local Languages on Arabic Education: A Linguistic Approach/ Ø£Ø«Ø± Ø§Ù„Ù„ØºØ§Øª Ø§Ù„Ù…ØÙ„Ù‘ÙŠÙ‘Ø© Ø§Ù„Ù†ÙŠØ¬ÙŠØ±ÙŠÙ‘Ø© ÙÙŠ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø¹Ø±Ø¨ÙŠ: Ù…Ø¯Ø®Ù„ Ù„ØºÙˆÙŠÙ‘ - Salaty, Abubakar Abdullah; Abdullahi, Yaqub Alhaji (Ijaz Arabi Journal of Arabic Learning, 2020)
The history of Arabic education in Nigeria is connected to the emergence of Islam which was embraced by Nigerians through the Arab traders. Nigeria as nation, has more than 400 indigenous local languages out of which the most common of the local languages are Hausa, Yoruba and Igbo. Other major languages are Fulfulde, Kanuri, Ibibio, Tiv, Efik and Nupe while English is considered as the country’s official language. As Muslims, it is necessary to acquire Arabic education in order to perform religious obligations such as the five time daily prayer and other basic Arabic knowledge for the in-depth understanding of Islam. It is however pertinent to note at this juncture that Arabic language, in an environment where local languages are predominantly spoken is established in the educational system. The researchers therefore aimed at investigating and examining the influence of the Nigerian local languages on Arabic education using a linguistic approach. Two local languages; Hausa and Yoruba were purposively selected among other local languages for the study, while findings and recommendations were made at the end of this work.